Aerosol inhalation of dimeric artesunate phospholipid-conjugated liposomes ameliorates inflammation, fibrosis, and ferroptosis in neonatal mice with hyperoxia-induced lung injury - Guan, Rong; Chen, Yu; Yu, Qianqian; Yu, Bingrui; Chen, Shuyu; Jia, Siyuan; Wang, Huifang; Cheng, Huaiping; Tian, Zhaofang (Frontiers in Pharmacology, 2025)
Bronchopulmonary dysplasia (BPD), a chronic lung condition that impacts preterm infants, results in persistent lung damage with limited therapeutic interventions available. Artemisinin, a bioactive compound derived from Artemisia annua, a member of the Asteraceae family, exhibits potent anti-inflammatory and anti-fibrotic characteristics and has been proven to confer protective benefits against acute lung injuries triggered by various factors. However, its potential impact on BPD and the mechanisms involved are not fully understood. This research examines the function and fundamental processes of dimeric artesunate phospholipid-conjugated liposomes (Di-ART-GPC) in BPD. In the in vivo experiments, 48 male neonatal C57BL/6 mice were arbitrarily divided into four cohorts: air (NC cohort), air + Di-ART-GPC (NA cohort), hyperoxia (HO cohort), and hyperoxia + Di-ART-GPC (HA cohort). Mice in the NC and NA cohorts were exposed to normoxic conditions (21% O2) from birth, while those in the HO and HA cohorts were subjected to hyperoxic conditions (95% O2) for 7 days. On the eighth day, NC and NA mice were administered double-distilled water (ddH2O 4 mL), while HO and HA mice received Di-ART-GPC (0.5 mg dissolved in 4 mL ddH2O) via inhalation once daily for 3 days. Lung tissues and serum were harvested on postnatal day 11. Histological evaluations included HE staining for alveolar structure assessment and RAC count and inflammation score quantification; Masson staining for fibrosis evaluation; immunohistochemistry and real-time quantitative PCR (RT-qPCR) for detecting TGF-β1 and α-SMA expression; and ELISA for measuring TNF-α and IL-6 levels. Additional assays quantified superoxide dismutase (SOD), malondialdehyde (MDA), and glutathione (GSH) levels, while immunofluorescence and RT-qPCR assessed Gpx4 expression. For the in vitro component, RAW264.7 macrophages were categorized into the same four cohorts based on culture conditions. Cells in the NC and NA cohorts were cultured under normoxic conditions, while those in the HO and HA cohorts were exposed to 95% O2 for 24 h, following treatment with Di-ART-GPC at 1.25 µM. The supernatant and cells were harvested for subsequent examination. ELISA was employed to measure TNF-α, IL-6, and TGF-β1 levels in the supernatant, while Western blot and RT-qPCR were employed to assess Gpx4 expression in RAW264.7 cells. In vivo findings demonstrated that, in contrast to the NC cohort, the HO cohort exhibited disrupted alveolar architecture, widened alveolar spaces, reduced RAC values, and elevated inflammation and fibrosis scores (p < 0.05). Additionally, the HO cohort demonstrated elevated levels of IL-6 and TNF-α (p < 0.05), higher mRNA expression of TGF-β1 and α-SMA (p < 0.05), reduced SOD activity, diminished GSH content (p < 0.05), and diminished GPX4 protein expression (p < 0.05). Administration of Di-ART-GPC markedly improved these parameters (all p < 0.05). Similarly, in vitro experiments revealed that Di-ART-GPC treatment reduced IL-6, TNF-α, and TGF-β1 levels in hyperoxia-exposed RAW264.7 cells (p < 0.05) and enhanced GPX4 expression (p < 0.05). These findings indicate that Di-ART-GPC demonstrates safeguarding properties against hyperoxia-induced lung damage, potentially by mitigating inflammation and fibrosis in lung tissues and reducing macrophage ferroptosis in hyperoxia-induced BPD.